Alginate and γ-polyglutamic acid hydrogels: Microbial production strategies and biomedical applications. A review of recent literature - Tania Castillo; Celia Flores; Holjes Salgado-Lugo; Carlos F. Peña; Enrique Galindo (Electronic Journal of Biotechnology, 2023)
Hydrogels are three-dimensional networks of hydrophilic polymers. In general, these structures can be soft, elastic, porous and can absorb high quantities of water. Due to these characteristics, there is a growing interest in the use of hydrogels in diverse areas, from bioremediation to applications in the biomedical field. Although hydrogels can be elaborated with natural and synthetic polymers, natural polymers are attracting attention for their use in the biomedical and pharmaceutical fields. Alginate and γ-polyglutamic acid (γ-PGA) are microbial polymers, which show a great potential for hydrogel elaboration because of their biocompatibility that positioned them in emerging technologies, such as tissue engineering, microencapsulation, and soft robotics; these applications require specific characteristics of hydrogels in terms of their mechanical resistance, swelling capability, flexibility, softness, and stiffness. Thus, there is an emerging interest in the microbial production of alginates and γ-PGA, where it is possible to change their physicochemical and thermomechanical characteristics by the manipulation of the culture growth conditions of the microbial producers that can be oriented to specific applications. In this review, the chemical composition of biopolymers, hydrogel structure, the applications of hydrogels of alginates and γ-PGA, as well as their advantages and limitations are described; besides, the bacterial production of these polymers and the growth conditions that modify their chemical composition, are discussed.How to cite: Castillo T, Flores C, Salgado-Lugo H, et al. Alginate and γ-polyglutamic acid hydrogels: Microbial production strategies and biomedical applications. A review of recent literature. Electron J Biotechnol 2023;66. https://doi.org/10.1016/j.ejbt.2023.09.001.